ТАЛАБАЛАРДА ЭЛЕМЕНТАР ЗАРРАЛАРНИНГ ФУНДАМЕНТАЛ ХОССАЛАРИ ҲАҚИДАГИ ТАСАВВУРЛАРИНИ ШАКЛЛАНТИРИШДА ЗАМОНАВИЙ АХБОРОТ ТЕХНОЛОГИЯЛАРИДАН ФОЙДАЛАНИШ - Насриддинов, К.; Орынбетов, Н.; Балтабаев, Ж. (SCIENCE and SOCIETY, 2017)
The article deals with the study of using of efective methods and creation of electronic study complexes, the fundamental peculiarities of elementary particles in teaching students in the course of Physics of elementary particles in the continuous system of education.